Technique for contingency monitoring and voltage collapse prediction - Moghavvemi, M.; Omar, F.M. (IEE Proceedings, 1998)
Investigation and online monitoring of power system stability have become vital factors to electric utility suppliers. At present power system utilities operate very close to the limit of system stability owing to an increasing number of new economic and environmental restrictions. Researchers have been trying to find out the most effective way for online system status monitoring, so that necessary precautions can be taken prior to voltage collapse. Several methods have been proposed for analysing voltage collapse phenomena. An effective method for online system status monitoring and thus voltage collapse prediction is described. The basic methodology implied in this technique is the investigation of each line of the system through calculating line stability indices. The proposed method was tested on the IEEE 24-bus reliability test system and has been found to be accurate and precise in voltage collapse prediction. A comparative study with other methods has also been carried out indicating that the proposed method has some advantages over the others.